PERFORMANCE OF T&D AND CROSS-BRED PIGS UNDER FIELD CONDITION - J. HUSSAIN3, R. ISLAM1 ; P. NATH2 (Indian Journal of Animal Production and Management, 2017)
A study was undertaken to record the productive and reproductive performance of T&Dand cross-bred (T&D X Assam Local) pigs under field condition of Assam. A total of 5numbers of farmers were selected randomly and purposively on the basis of theirexperience in pig farming and who must possessed at least 3 numbers of T&D and 3numbers of cross-bred pigs with one male and two females of each genetic groups of pig.The pigs were reared under free range scavenging system of rearing. The piglets weremonitored regularly for their health status and their monthly body weight was recorded up to9 months of age. Some of the important reproductive traits such as age at puberty (days),body weight at puberty (kg.), age at first farrowing, gestation period (days), litter size, bodyweight of piglets at birth (kg.), pre-weaned litter survivability (%), farrowing intervals (days)and body weight at 12 months of age (kg.) were also recorded. From the above study it maybe inferred that T&D pigs are significantly better in terms of productive and reproductiveperformance than cross-bred under field condition of Assam.